Skeletonized internal thoracic artery is associated with lower rates of mediastinitis in elderly undergoing coronary artery bypass grafting surgery - Sá,Michel Pompeu Barros de Oliveira (2011)
BACKGROUND AND OBJECTIVES: Mediastinitis is a serious complication of median sternotomy and is associated to significant morbidity and mortality. The aim of this study is to identify which option of harvesting internal thoracic artery (ITA), pedicled or skeletonized, is associated with lower rates of mediastinitis after coronary artery bypass grafting surgery (CABG) in elderly, in the Division of Cardiovascular Surgery of PROCAPE. METHODS: Retrospective study of 160 elderly who underwent consecutive CABG between May 2007 and June 2011. Eleven preoperative variables, four intraoperative variables and eight postoperative variables possibly involved in the development of postoperative mediastinitis were evaluated between two groups: CABG with skeletonized ITA (n=80) and pedicled ITA (n=80). Univariate and multivariate logistic regression analyses were applied. RESULTS: The incidence of mediastinitis was 6.8% (n=11), with a lethality rate of 54.5% (n=6). The skeletonized ITA group were more exposed than pedicled ITA group to obesity (n=12 vs. n=4; 15% vs. 5%; P=0.035) and multiple transfusions (n=25 vs. n=11; 31.2% vs. 13.7%; P=0.008). The pedicled ITA group presented a greater risk of mediastinitis after CABG than skeletonized ITA group (n=10 vs. n=1; 12.5% vs. 1.2%; Unadjusted OR 11.3; 95% CI 1.4 - 241.5; P=0.008). In multivariate analysis, this difference maintained statistically significant (Adjusted OR 5.2; 95% CI 1.5-495.8; P=0.012), being considered an independent association. CONCLUSIONS: We suggest that elderly should be considered for strategies to minimize risk of infection. In elderly that undergo unilateral ITA, the problem seems to be related to how ITA is harvested. Elderly should always be considered for use of skeletonized ITA.